2015
DOI: 10.1589/jpts.27.1233
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the intensity of physical activity and depressive symptoms among Korean adults: analysis of Korea Health Panel data

Abstract: [Purpose] The aim of this study was to examine the relationship between the intensity of physical activity and symptoms of depression. [Subjects and Methods] We analyzed the influence of different intensities of physical activity on depressive symptoms using the data of 12,350 adults over the age of 20 years who had completed the 2011 Korea Health Panel. After controlling for confounding variables, a multivariable logistic regression analysis was conducted to identify the association between the intensity of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…Studies have shown a negative relation between physical activity and age among the elderly . Studies in the literature also suggest that there is an important relation between the physical activity and sex and chronic illnesses of the elderly .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown a negative relation between physical activity and age among the elderly . Studies in the literature also suggest that there is an important relation between the physical activity and sex and chronic illnesses of the elderly .…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Studies have shown a negative relation between physical activity and age among the elderly. 25,31,[38][39][40] Studies in the literature also suggest that there is an important relation between the physical activity and sex and chronic illnesses of the elderly. 25,31,[38][39][40][41] These results support the hypothesis that depression and personal characteristics (eg, age, sex, education level) affect the physical activity of the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Walking slowly or at a moderate pace for the use of public transportation were included in the light physical activity. We used the guidelines suggested by Noh et al 21 to divide the participants into exercising and non-exercising groups based on the number of days and hours in which they took part in physical activity. The intensity of the physical activity was based on the physical activity recommendations of the Centers for Disease Control and Prevention and the American College of Sports Medicine.…”
Section: Methodsmentioning
confidence: 99%
“…However, the antidepressant effect of exercise is, in general, still speculative. Although it was observed that acute exercise of any intensity significantly improved depressive symptoms in women (Meyer et al, 2016), other sources have shown that correlations between physical activity and depression depend on the intensity of the exercise (Noh et al, 2015). After all, the results of study showing the most beneficial behavioral effects of exercise, including antidepressant effects, were achieved by using prolonged exercise protocols with mild (erobic) intensity (Joksimović et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%